Determinants of value creation from organizational performance-based view: Implications for IT industry in the Post-Covid-19 World - Wadhawan, Saurabh; Meadows, CJ; Abraham, Christopher (The journal of contemporary issues in business and government, 2021)
Purpose – The purpose of this study is to identify the variables that drive value creation in the Information Technology (IT) industry specifically, in the post-Covid-19 world. Design/methodology/approach - This study has synthesized existing literature through which it identifies the variables driving value creation in the IT industry. Findings - The results of the study show that competitive advantage, cross-disciplinary communication, and diversity drive value creation in the IT industry. Furthermore, the discussion extends organizations' absorptive capacity through the means of integration, learning, and reconfiguring knowledge by assimilating the knowledge process to sense and seize vital opportunities in the market, enablingservice innovation practices outcome, driving enterprise agility by leading digital adoptions in the Post-Covid-19 times,yielding the higher organization value by the extent of social-network heterogeneity (SNH) and focussing on the principle of “the strength of weak ties”are the abilities of an organization to react to a crisis. Research limitations/implications – This study proposes that this article should help the IT industry and the organizations underneath to achieve greater agility, stability through the extent of IT infrastructure, IT human resource, and IT knowledge management, focusing on cross-disciplinary as a collection of practices over a) intentional learning, b) strategic leadership, and c) transforming practices into integrating systems and embracing design thinking (DT) by encompassing emotional intelligence, integral intelligence, and experiential intelligence approaches, in these post-Covid-19 times more effectively and confidently. Additionally, leveraging absorptive capacity is a key resource in developing and increasing organizations' knowledge pools. Originality/value – This study offers a theoretical platform for the study ofvalue creation in the IT industry. The present study is the first step towards integrating the elements of value creation with dynamic capabilities to enhance the absorptive capacity of an organization, promoting entrepreneurial behavior and diversity management capabilities. Furthermore, this study ascertains the role of market dynamism, Schumpeter's innovation dimensions, Maslow's hierarchy of needs, constructivism, organizational learning,resilience-enhancing diversity management (REDM), strategic human resource management (HRM),and resource- based view as implementation models for the variables identified.